Opening Teaching To Motivate Students In Learning English - Sani, Riny Dwitya; Asty, Herfyna (JUPE : Jurnal Pendidikan Mandala, 2023)
The research is to find out the opening activities of teaching carried out by English teachers to motivate students. This type of research is qualitative in nature with a descriptive method. Data collection techniques were carried out through observation and field notes. Based on the results of research and discussion of opening teaching activities by English teachers to motivate students in class, it can be concluded that the skills of English teachers in class in opening learning include: arousing students' attention, namely variations in teaching styles, use of instructional media and interaction patterns. , namely excited and enthusiastic, arousing curiosity, and generating conflicting ideas. Giving references, namely conveying learning objectives and determining activity steps. Demonstrating relevance, namely determining stepping stones, generating new knowledge, providing continuous material. Regarding all of these indicators, the researcher found that the English teacher's opening teaching activities had been carried out although not all the indicators and results of the study found that the teacher motivated student learning to open teaching activities by creating an active learning process such as making eye contact, providing discussion with questions and then students answer according to their knowledge, the teacher's character is friendly, and explains the material with clear intonation.